Grammaticalized Use of Participles of Quechua and Aymara Verbs Equivalent to the Verb to say - Ferrell Ramírez, Marco A. (2020)
This paper describes and explains the behaviour of the participles of the verb ‘to say’ in Quechua and Aymara, nisqa and sata, respectively, that with a particular right-bound syntax serve the function of highlighting a nominal element of the sentence. These nominal components can carry case and possessor suffixes. This usage has been recorded in the cultured and formal language since the 15th century.